2021–2022 Florida Citrus Production Guide: Citrus Black Spot - Megan M. Dewdney; Callie Walker; Pamela D. Roberts; Natalia A. Peres (EDIS)
Sections: regulatory considerations; growers, caretakers, harvesters, and haulers; processing and packing facilities and haulers, disposal of citrus debris; Interstate shipment of fruit; export shipment of fruit; regulatory remarks; and recommended chemical controls